Lifestyle Perceptions among Middle - Aged Obese Women - Živilė Vasiliauskaitė; Diana Karanauskienė (Lithuanian Sports University, 2018)
Background. The aim of the study was to establish the perceptions of lifestyles among middle-aged obese women. Methods. Data collection method was semi-structured face-to-face interview. Interview guide was based on short form 36 (SF-36), long form of IPAQ and previous research (Bukman et al., 2014).  Results. All obese women of our study feel inferiority complex due to their physical appearance, feel dissatisfied with themselves trying to hide their appearance, discomfort, and disadvantages. They have a lot of health problems: joint pain, increased cholesterol level, increased blood pressure, heart beat rate, dyspnoea, as well as chronic diseases such as type 2 diabetes, thyroid gland dysfunction and sleep disorders. All the subjects both had poor eating habits and ate inadequate food. Some of the participants ate a lot before bedtime and skip breakfast. The physical activity is limited and reduced of all subjects. Conclusions. The relationship between excess weight and psychological well-being is complex, encompassing physical, social and psychological factors. All obese women of our study feel inferiority complex due to their physical appearance, dissatisfed with themselves. They complained of cardiovascular problems, sleep disorders and chronic diseases. The physical activity was limited and decreased. Also, such a great weight excess caused a discomfort in their daily life. Obese women in our study negatively view smoking eﬀects, but they tolerate or even have positive attitudes to alcohol consumption, though they acknowledge that alcohol increases their weight. Malnutrition is  most common problem of our respondents. They both had poor eating habits and ate inadequate food. Some of the participants ate a lot before bedtime and skip breakfast. A lot of participants reported about their negative attitude to their diet, but this attitude did not always act like a stimulus to change. Most of respondents could not fnd the time or motivation to engage in the adequate physical activity. They wanted to increase their physical activity, but found excuses not to do that - their excess of weight, lack of time, as well as laziness, passivity - the main causes of their inactivity or poor physical activity. Keywords: obesity-related health problems, lifestyle perceptions, adequate physical activity.